Improvement of Technology of Gypsum Production Raw Materials and Products in Production - Mahmudov Rafik Amonovich; Shukrullayev Javohir Oybek ugli; Ereshboyev Husniddin Fazliddinovich; Adizova Muqaddas Odil kizi (Zien Journals, 2022)
Gypsum materials are one of the most effective and promising types of building materials, the production of which currently requires expansion and modernization, taking into account the latest achievements of science. This article focuses on the production of gypsum products and the improvement of production technology
Keywords: binders; technical properties; gypsum products; phosphogypsum